A New Numerical Algorithm for Two-Point Boundary Value Problems. (30th June 2014) - Guo, Lihua; Wu, Boying; Zhang, Dazhi
Abstract : We present a new numerical algorithm for two-point boundary value problems. We first present the exact solution in the form of series and then prove that the n -term numerical solution converges uniformly to the exact solution. Furthermore, we establish the numerical stability and error analysis. The numerical results show the effectiveness of the proposed algorithm.